The Slovak Concepts of Integration - Halász, Iván (The Development of European and Regional Integration Theories in Central European Countries, 2022)
The first part of this chapter deals with the factors that determined Slovak national development; conflict between Catholics and Protestants played an important role in this process. Another important factor was the Czech-Slovak linguistic and cultural proximity, which allowed continuous interaction, but slowed independent Slovak identity-building processes. Slovaks lived for a long time on the northern periphery of the old Kingdom of Hungary, where, despite their relatively high number of people, they did not have autonomy. Slovak politics had to settle relations with the Czechs and Hungarians in the 19th and 20th centuries. The Slovaks also tried to geographically define the region they inhabited. An important role in this process was played by its proximity to the Danube and the mountainous character of the country under the Carpathians. In building cultural and political identity, however, the sense of Slavic unity, which Hungarian politics called Panslavism, has traditionally played an important role. Most Slovak political concepts dealt with federation. Russophilism was strong in Slovak politics for a long time, but the 19th century, Czech-Slovak cooperation seemed more realistic. Czechoslovakia was finally born as a result of the First World War. After 1918, the democratic Western orientation was strengthened, and several politicians considered cooperation along the Danube important. In the shadow of the Soviet and German threats, Central Europe concepts were born. The most famous is former Prime Minister Milan Hodža’s concept, which was conceived during his US emigration. After the Second World War, all of Czechoslovakia became part of the Soviet Eastern Bloc. Other orientations have long been taboo. Solidarity in Central Europe, on the other hand, has strengthened in anti-communist opposition circles. The country’s Western integration began after 1989, but the pro-Russian political orientation was also strong. In these years, Central European solidarity and identity have promoted democratic orientation and European Union integration.KEYWORDS: assimilation, Carpathia, Danube-region, Europe, nationalism, slavism, Slovakia